Diagnóstico del clima laboral de los servidores administrativos del Gobierno Autónomo Descentralizado del Cantón Quilanga, año 2021 - Ortiz Yaguana, Melissa Josefina (2022)
Today the work environment has become an issue of great importance within the institutions, since having a good work environment will be reflected in a good performance of its employees, which leads to achieve the institutional objectives. Therefore, this research was developed with the purpose of establishing the relationship between the work environment and the performance of the administrative employees of the Decentralized Autonomous Government of Canton Quilanga during the year 2021, starting from its current diagnosis and identifying the factors of the work environment and its relationship with the performance of the personnel, which allowed new proposals for its improvement. In this context, a descriptive and explanatory non-experimental research was carried out. The population under study was a total of 26 administrative employees, using a survey consisting of 53 questions, an interview with the head of human resources and a direct observation form applied by the researcher. The method applied to verify the relationship between the two variables studied was Fisher's exact test, where with a P-value equal to 0.017 statistical evidence was found to reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha) "The dimensions of performance are NOT independent of the work climate factors". The study concluded that the work environment does have a relationship with work performance, therefore, according to the opinions of the employees regarding the environment that surrounds them, it was possible to make proposals to improve their performance in those aspects that cause them dissatisfaction.